2003
DOI: 10.1111/j.1741-3729.2003.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Adaptation of Military Families: An Empirical Test of a Community Practice Model*

Abstract: This study used structural equation modeling to examine a strengths-based, community practice model to explore the relationship between formal and informal community-based social networks and family adaptation in military communities. ''Sense of community'' was examined as a critical mediating variable. Results provide support for the practice model. Several important insights were revealed about the strength and nature of pathways between components in the model. Results suggest that communities (including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 34 publications
3
110
1
1
Order By: Relevance
“…Twenty-one items assessed participants' sense of shared mission, teamwork, unity, and connectedness in the community (e.g., "Civilian spouses/active duty members find it easy to make connections with other families"). Low community cohesion is a predictor of neighborhood disorder and a risk factor of family violence (e.g., Bowen et al, 2003;. Items are rated on a 6 point scale from strongly disagree to strongly agree (a ¼ 0.96).…”
Section: Community Constructsmentioning
confidence: 99%
“…Twenty-one items assessed participants' sense of shared mission, teamwork, unity, and connectedness in the community (e.g., "Civilian spouses/active duty members find it easy to make connections with other families"). Low community cohesion is a predictor of neighborhood disorder and a risk factor of family violence (e.g., Bowen et al, 2003;. Items are rated on a 6 point scale from strongly disagree to strongly agree (a ¼ 0.96).…”
Section: Community Constructsmentioning
confidence: 99%
“…Conversely, in a sample of soldiers deployed to Kosovo, Britt et al (2007) found lack of confidence in unit leadership was predictive of postdeployment depression. Bowen et al (2003) found a somewhat different, but equally important, effect of unit leadership; in their studies of active duty Air Force personnel, leadership influenced service members' sense of community, which in turn impacted well-being and satisfaction of service members and their families.…”
Section: Introductionmentioning
confidence: 95%
“…Généralement, l'appui de la famille suffit pour que le soldat puisse reprendre son ancienne routine (Bowen, et collab., 2003). Toutefois, lorsqu'un soldat présente des symptômes de détresse psychologique, il n'est pas rare que la famille, la conjointe en particulier, subisse un traumatisme secondaire (Dirkzwager, et collab., 2005).…”
Section: La Réintégration Des Pères Militaires à Leur Foyerunclassified